Frequency of Cystic Duct Anatomical Variations on ERCP- A Retrospective Cross-Sectional Study - Sidra Rasheed; Muhammad Ahsan Farooq; Khurram Malik; Hooria Rehman; Hafiz Irfan Mushtaq; Akif Dilshad; Ghias Un Nabi Tayyab (Pakistan Journal of Health Sciences, 2026)
Cystic duct (CD) anatomical variations are common, but they frequently go unrecognized. Their prevalence differs among different studies. A proper understanding of these variations is important before performing any percutaneous, surgical, or endoscopic interventions to avoid complications. Objectives: To evaluate the frequency of anatomical variations of cystic duct insertion observed on endoscopic retrograde cholangiograms. Methods: A total of 500 cholangiograms (2020-2022) fulfilling the inclusion criteria were analyzed retrospectively for various CD insertion patterns from the Endoscopy suite of Lahore General Hospital, Lahore, after approval from the IRB. Patient information, including age, gender, and indication of ERCP were also recorded. Data were processed on SPSS v.25. Results of continuous measurements were expressed as mean ± SD (min, max), and results of categorical measurements were presented as number (%). Results: Among 500, there were 45% male and 55% female. Normal cystic duct mid-lateral insertion was seen in 62.2% of patients, while 37.8% showed anatomical variations. Among these variations, the most frequent one was low medial (15.4%), followed by middle medial (8.6%) and high lateral (7%). Conclusions: The study identified a high frequency of CD variations, thus highlighting the importance of imaging for the identification of these variations before performing any surgical or endoscopic procedures.